1999
DOI: 10.1212/wnl.52.3.588
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of MS clinical phenotypes using conventional and magnetization transfer MRI

Abstract: Pathology in patients with clinically isolated syndromes is confined to modest tissue damage in the lesions seen on T2-weighted scans. Severe damage is important for the later development of disability. However, microscopic damage in normal-appearing white matter may be a major contributor to disability in primary progressive MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
169
3

Year Published

2000
2000
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 204 publications
(187 citation statements)
references
References 37 publications
15
169
3
Order By: Relevance
“…Such measures are sensitive in depicting subtle abnormalities in NAWM and NAGM and convincing evidence has emerged that increasing abnormality in these tissues is associated with clinical progression. 99,100 However, these subtle MR changes are pathologically nonspecific and could potentially represent the effects of inflammation, gliosis, or axonal loss, all of which occur in NAWM. 4,101 Although they may be valuable for monitoring clinically relevant disease progression they should not be considered as specific markers of neurodegeneration.…”
Section: Other Measuresmentioning
confidence: 99%
“…Such measures are sensitive in depicting subtle abnormalities in NAWM and NAGM and convincing evidence has emerged that increasing abnormality in these tissues is associated with clinical progression. 99,100 However, these subtle MR changes are pathologically nonspecific and could potentially represent the effects of inflammation, gliosis, or axonal loss, all of which occur in NAWM. 4,101 Although they may be valuable for monitoring clinically relevant disease progression they should not be considered as specific markers of neurodegeneration.…”
Section: Other Measuresmentioning
confidence: 99%
“…MS lesions also have lower MTR values (typically 20 pu in this image dataset) and, therefore, the threshold selected was such that voxels in visible lesions were not removed by this process. Other workers [1]- [5] have used thresholds in a similar manner; we chose this after experimentation, selecting an aggressive value to reduce partial volume effects with CSF.…”
Section: ) Thresholdingmentioning
confidence: 99%
“…On the contrary, magnetic resonance imaging (MRI) has provided combersome and controversial results. In detail, the majority of the studies showed that the load of T 2 -visible lesions is similar between patients with BMS and those with other disease phenotypes, whereas the extent of normal-appearing brain tissue (NABT) damage was found to be less pronounced in patients with BMS than in other forms of the disease in some studies [Davie et al, 1999;De Stefano et al, 2006;Falini et al, 1998;Filippi et al, 1996Filippi et al, , 1999Filippi et al, , 2000, but not in others [Brass et al, 2004;Droogan et al, 1999;Horsfield et al, 1996;Traboulsee et al, 2003].…”
Section: Introductionmentioning
confidence: 99%
“…Such an approach was driven by two considerations: (a) to investigate cortical functional changes in patients with a ''real'' benign course (i.e., with no locomotor and cognitive impairment), and (b) to study the underlying functional cortical correlates of brain-mediated clinical aspects (contrary to cognition, locomotor ability is indeed likely to be associated to both brain and spinal cord integrity). Differently from previous studies based on an ''overall'' assessment of brain damage [Brass et al, 2004;Davie et al, 1999;De Stefano et al, 2006;Droogan et al, 1999;Falini et al, 1998;Filippi et al, 1996Filippi et al, , 1999Filippi et al, , 2000Horsfield et al, 1996;Traboulsee et al, 2003], we investigated the structural correlates of fMRI abnormalities, by using diffusion tensor (DT) tractography, since it is likely that damage of ''strategic'' white matter (WM) fiber bundles of the brain might be more strictly linked to functional cortical changes than ''overall'' NABT damage. DT MRI provides quantitative data on water molecular motion, a marker of tissue structure and organization.…”
Section: Introductionmentioning
confidence: 99%